Relationship Between Inflow Impairment and Skin Oxygen Availability to the Upper Limb During Standardized Arm Abduction in Patients With Suspected Thoracic Outlet Syndrome - Hersant, Jeanne; Lecoq, Simon; Ramondou, Pierre; Papon, Xavier; Feuilloy, Mathieu; Abraham, Pierre; Henni, Samir (Frontiers in Physiology, 2022)
Objective Thoracic outlet syndrome (TOS) should be considered of arterial origin only if patients have clinical symptoms that are the result of documented symptomatic ischemia. Simultaneous recording of inflow impairment and forearm ischemia in patients with suspected TOS has never been reported to date. We hypothesized that ischemia would occur in cases of severely impaired inflow, resulting in a non-linear relationship between changes in pulse amplitude (PA) and the estimation of ischemia during provocative attitudinal upper limb positioning. Design Prospective single center interventional study. Material Fifty-five patients with suspected thoracic outlet syndrome. Methods We measured the minimal decrease from rest of transcutaneous oximetry pressure (DROPm) as an estimation of oxygen deficit and arterial pulse photo-plethysmography to measure pulse amplitude changes from rest (PA-change) on both arms during the candlestick phase of a “Ca + Pra” maneuver. “Ca + Pra” is a modified Roos test allowing the estimation of maximal PA-change during the “Pra” phase. We compared the DROPm values between deciles of PA-changes with ANOVA. We then analyzed the relationship between mean PA-change and mean DROPm of each decile with linear and second-degree polynomial (non-linear) models. Results are reported as median [25/75 centiles]. Statistical significance was p < 0.05. Results DROPm values ranged −11.5 [−22.9/−7.2] and − 12.3 [−23.3/−7.4] mmHg and PA-change ranged 36.4 [4.6/63.8]% and 38.4 [−2.0/62.1]% in the right and left forearms, respectively. The coefficient of determination between median DROPm and median PA-change was r2 = 0.922 with a second-degree polynomial fitting, but only r2 = 0.847 with a linear approach. Conclusion Oxygen availability was decreased in cases of severe but not moderate attitudinal inflow impairments. Undertaking simultaneous A-PPG and forearm oximetry during the “Ca + Pra” maneuver is an interesting approach for providing objective proof of ischemia in patients with symptoms of TOS suspected of arterial origin.